Microbiological profiling and knowledge of food preservation technology to support guidance on a neutropenic diet for immunocompromised patients - De Bock, Thomas; Jacxsens, Liesbeth; Maes, Femke; Van Meerhaeghe, Svenya; Reygaerts, Marina; Uyttendaele, Mieke (Frontiers in Microbiology, 2023)
The current society consists of an increasing number of people vulnerable to infections. For certain people with severe immunodeficiency, a neutropenic or low-microbial diet is being prescribed, which substitutes high-risk foods that are more likely to contain human (opportunistic) pathogens with lower-risk alternatives. These neutropenic dietary guidelines are typically set up from a clinical and nutritional perspective, rather than from a food processing and food preservation perspective. In this study, the current guidelines in use by the Ghent University Hospital were evaluated based on the current knowledge of food processing and preservation technologies and the scientific evidence on microbiological quality, safety, and hygiene of processed foods. Three criteria are identified to be important: (1) the microbial contamination level and composition; (2) the potential presence of established foodborne pathogens such as Salmonella spp. (to which a zero-tolerance policy is recommended); and (3) an increased vigilance for L. monocytogenes as an opportunistic foodborne pathogen with a high mortality rate in immunocompromised individuals (to which a zero-tolerance policy should apply). A combination of these three criteria was used as a framework for the evaluation of the suitability of foodstuffs to be included in a low-microbial diet. Differences in processing technologies, initial contamination of products, etc., however, lead to a high degree of variability in microbial contamination and make it difficult to unambiguously accept or reject a certain type of foodstuff without prior knowledge of the ingredients and the processing and preservation technologies applied during manufacturing and subsequent storage conditions. A restricted screening on a selection of (minimally processed) plant-based foodstuffs on the retail market in Flanders, Belgium supported decision-making on the inclusion of these food types in a low-microbial diet. Still, when determining the suitability of a foodstuff to be included in a low-microbial diet, not only the microbiological status but also nutritional and sensorial properties should be assessed, which requires multidisciplinary communication and collaboration.